Experimental Study on the Temperature Field of Cold Region Tunnel under Various Groundwater Seepage Velocities. (10th December 2020) - Cao, Shiding; Lu, Taishan; Zheng, Bo; Zhang, Guozhu
Abstract : Groundwater seepage significantly affects the temperature field of a cold region tunnel. Laboratory model tests are carried out to evaluate its effects, yielding four main results. First, groundwater seepage can increase tunnel air temperature and decrease the thickness and length of the tunnel insulation layer. Second, groundwater seepage and tunnel ventilation exert a coupling effect on the surrounding rock temperature. This effect is related to the surrounding rock depth. Third, the influence of the groundwater seepage velocity on the temperature of the interface between the lining and surrounding rock demonstrates a spatial difference, and the groundwater seepage leads to an uneven temperature distribution at the interface between the lining and surrounding rock. Furthermore, under groundwater seepage, the shape and size of the tunnel cross section have significant effects on the interface temperature. Fourth, the cold region tunnel has an antifreezing capability that is mainly related to the frost heaving of the surrounding rock and the groundwater seepage velocity. This capability should be fully utilized in the design of cold region tunnels. The experimental data presented can be used to verify the reliability of the theoretical calculation model for tunnel temperatures in cold regions.